Asymmetric Synthesis of Oxa-spirocyclic Indanones with Structural Complexity via an Organocatalytic Michael–Henry–Acetalization Cascade - Xie, Xin; Peng, Cheng; Leng, Hai-Jun; Wang, Biao; Tang, Zheng-Wei; Huang, Wei (Synlett, 2014)
The highly enantioselective preparation of drug-like oxa-spirocyclic indanone derivatives employing a multicomponent cascade reaction is described. This approach utilizes an organocatalytic Michael reaction followed by a Henry–acetalization sequence that yields the desired chiral spirocyclic backbone, bearing four contiguous stereogenic centers and multiple functional groups, in good yields and high stereoselectivities (up to 99% ee and 95:5 dr).
Keywords: organocatalysis; chiral indanone; oxa-spirocycles; tandem reactions; asymmetric synthesis